1997
DOI: 10.1111/j.1439-0523.1997.tb02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Yielding ability, yield stability, and quality of exotic durum wheat germplasm in Sicily

Abstract: A set of 20 accessions of durum wheat (Trilicum lurgidum L., durutn group), which mostly included exotic landraces from various Mediterranean countries, and four Italian improved varieties were evaluated for grain yield in five environments and for quality traits in two environments of Sicily. Glutenin composition was also assessed electrophoretically on six seeds per entry. The cultivars differed (P ^ 0.01) for yield, protein content and sodium dodecyl sulphate (SDS-sed) sedimentation volume, in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
13
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 9 publications
14
13
0
1
Order By: Relevance
“…In the present study, the importance of GEI varied among the analyzed quality parameters; GEI variation, although significant, was several times lower than that of genotype and environment and the lowest in relation to genotype was for grain hardness and hectoliter weight but in relation to environment for wet gluten content and also hectoliter weight (Table 3). Small effect of GEI on sedimentation value (SDS) and other quality characteristics was revealed among others by Lukow and McVetty (1991), Boggini et al (1997), Peterson et al (1998), Ames et al (1999), and Budak et al (2003). The results obtained in our experiments conducted in eight environments were similar to the results presented by Peterson et al (1998), which are based on experiments performed in replicated trials at 10 locations and two years (totally in 17 environments).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, the importance of GEI varied among the analyzed quality parameters; GEI variation, although significant, was several times lower than that of genotype and environment and the lowest in relation to genotype was for grain hardness and hectoliter weight but in relation to environment for wet gluten content and also hectoliter weight (Table 3). Small effect of GEI on sedimentation value (SDS) and other quality characteristics was revealed among others by Lukow and McVetty (1991), Boggini et al (1997), Peterson et al (1998), Ames et al (1999), and Budak et al (2003). The results obtained in our experiments conducted in eight environments were similar to the results presented by Peterson et al (1998), which are based on experiments performed in replicated trials at 10 locations and two years (totally in 17 environments).…”
Section: Discussionsupporting
confidence: 80%
“…Ames et al (2003) obtained the same result for the SDSS test but they found a significant V × N interaction for P. In contrast, Lerner et al (2006) detected no significant V × N interaction for P, and significant Y × V interaction for P and SDSS. Boggini et al (1997) found significant genotype-environment interaction for both quality parameters. The wide ranges of variation found for P and SDSS test were expected because the landraces analysed varied greatly in geographical origin and agro-morphological characters .…”
Section: Discussionmentioning
confidence: 94%
“…Also, these varieties usually display higher genetic diversity than modern cultivars. The ability to tap into that diversity depends on identifying those accessions containing alleles of interest (Boggini et al, 1997). The evaluation of landraces for quality and yield at low N rate can help to pre-select genotypes adapted to reduced N application.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding semolina quality variations due to different environments would be useful for improving pasta quality. Several studies carried out in Italy have also reported the high influence of environment and genotype x environment interaction in determining durum wheat quality (Mariani et al, 1995;Nachit et al, 1995;Boggini et al, 1997;Novaro et al, 1997). Other results (Miezan et al, 1977;Zhu and Khan, 2001) provide the evidence that interannual and multilocal variation on thousand-kernel weight and protein content are much more influenced by environmental conditions than by genotype.…”
Section: Discussionmentioning
confidence: 99%